Endophytic Fungus of Hendersonia sp: An alternative Biological Agent to Control Ganoderma in Oil Palm (Elaeisguineensis Jacq) - Dahang, Donatus (Agros Journal of Agriculture Science, 2019)
The research of using endophytic fungus of Hendersonia sp to prevent of Ganoderma (Ganoderma boniense) attacking oil palm (Elaeis guineensis Jacq) on seeds stadium had accomplished. The purpose of the research was to know the colonization of the Hendersonia in seedlings of oil palm that functions as a defensive agent of Ganoderma, so that the seedlings can be evaded of Ganoderma disease along their life. The beneficial of the research was to enhance knowledge of biological control of Ganoderma disease, particularly in oil palm seedlings, and also as sources of information in repairing the way of cultivations. The research was carried out in PTPN 3, Deli Serdang, North Sumatra, in two stages i. e application of Hendersonia in the field since Jun 2018 and samples checked in the Laboratory of Soil Science of North Sumatra University in February 2019. The Hendersonia was applied to 420 seeds in three different groups, 140 plants per group i.e 50gr G + 0gr R to each plant in group A, 50gr G + 40gr R to each plant in group B, and 0gr G + 40gr R for each plant in group C. The first application was in seedlings of three months old when they were transferred from pre-nursery to the main one on Jun 2018. The second and the third application were in the main nursery to the seedlings of six and nine months old. The Data of the research were analysed by descriptive way by account of the percentages of colonization in roots sections that were checked in the Laboratory, and Test-t to know the difference of colonization of Hendersonia in between the applications. Results shown, the average of Hendersonia colonization of application 3 (150 gr/ plant) was 9,33 which was higher than the application 2 (100 gr/ plant) 8,33.  There was a significant correlation in application 2 and 3 with the value of sig 0,032 < 0,05 and coefficient of correlate was 85,1%. However, because of the value of Sig. (2-tailed) > 0.05, so that there were no significant differences colonization of Hendersonia between applications 2 and 3. Therefore, the application 3 might used in the future.